2022
DOI: 10.3390/s23010403
|View full text |Cite
|
Sign up to set email alerts
|

IoT-Based Systems for Soil Nutrients Assessment in Horticulture

Abstract: Soil nutrients assessment has great importance in horticulture. Implementation of an information system for horticulture faces many challenges: (i) great spatial variability within farms (e.g., hilly topography); (ii) different soil properties (e.g., different water holding capacity, different content in sand, sit, clay, and soil organic matter, different pH, and different permeability) for different cultivated plants; (iii) different soil nutrient uptake by different cultivated plants; (iv) small size of mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 94 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…Postolache et al ( 2023 ) found that there is no large-scale or commercially available IoT system for horticulture and then proposed an IoT-based system for soil fertility evaluation in horticultural farms to aid in detecting plant stress and improve irrigation and fertilization decision process which needs not only the current value of soil nutrient but the historical nutrient data. The sensing nodes sense some soil and climate parameters and use Wi-Fi or LoRa for communication.…”
Section: Discussionmentioning
confidence: 99%
“…Postolache et al ( 2023 ) found that there is no large-scale or commercially available IoT system for horticulture and then proposed an IoT-based system for soil fertility evaluation in horticultural farms to aid in detecting plant stress and improve irrigation and fertilization decision process which needs not only the current value of soil nutrient but the historical nutrient data. The sensing nodes sense some soil and climate parameters and use Wi-Fi or LoRa for communication.…”
Section: Discussionmentioning
confidence: 99%
“…These solutions are mainly focused in the field of automating the irrigation process [15], [16]. Building a smart irrigation system requires a set of electronic devices that can be controlled by humans as well as communication with each other.…”
Section: Existing Smart Irrigation Solutions On the Market And Analys...mentioning
confidence: 99%
“…Under low-energy extraction conditions, the loosely bound, easily exchangeable forms of the compound are prevailingly extracted. In high-energy conditions, the strongly retained and part of the selectively retained exchangeable forms of the compound are also extracted [31,32].…”
Section: Introductionmentioning
confidence: 99%